Pengembangan Tari Zapin Kanak Beriya untuk Meningkatkan Kemampuan Motorik Kasar Anak Usia 4-6 Tahun di TK Negeri Pembina 3 Pekanbaru - Risma Elviani; Nurlita Nurlita; Zulkifli Nurdin (Journal on Education, 2024)
This study aims to develop Zapin Kanak Beriya Dance to improve gross motor skills of children aged 5-6 years in TK Negeri Pembina 3 Pekanbaru. The type of research used is RND (Research and Developmet) research with quantitative methods. The steps used are six stages, namely potential and problem, data collection, product design, design validation, design revision, product trial. The data analysis technique used is quantitative descriptive. The results of the study obtained media expert validation of 97.05%, material expert validation of 97.50%, dance expert of 87.50%, and educator expert of 91.47% with the Very Decent category. The results of the limited trial conducted were obtained by 74.38%, then an initial trial / pretest of 41.40% was carried out, after being given the zapin kanak dance beriya there was an increase, namely from the results of the final trial / posttest of 78.12% with the Eligible category. with the Eligible category. From the results of the study, it was concluded that Zapin Kanak Beriya Dance is suitable to be used as a physical activity to improve gross motor skills of children aged 5-6 years in TK Negeri Pembina 3 Pekanbaru.